Cycloplegic influence on the accuracy of autorefractometer in myopic and hyperopic children - Prabhakar, SK; Prathibha, KS; Angadhi, Pooja A; Singhal, Anuj Kumar; Ara, Raghavender Reddy; Naaz, A Shamsiya (Nepalese Journal of Ophthalmology, 2016)
Objective: To investigate the cycloplegic effect on the accuracy of TOPCON AR RM-8000B autorefractometer in children. Materials and methods: This study included 219 children of age 3 to 16 years. Topical 1% cyclopentolate hydrochloride was instilled for attaining cycloplegia. The children with the refractive error of –0.75 Diopter or more were grouped as myopic and more than +1.00 Diopter as hyperopic. Autorefraction was performed in addition to manual refraction. We used the XLSTAT and Medcalc statistics software. Results: Out of 219 children, 149 (68%) were emmetropic, 48 (22%) hyperopic and 22 (10%) myopic (n=70). Males and females constituted 29 (60.42%) and 19 (39.58%) respectively in hyperopic group where as 11 (54.55%) and 9 (45.45%) children were myopic. The means of ages of the children were 10.29 (+/- 2.96) and 13.14 (+/- 2.36) years in hyperopic and myopic groups respectively. Cycloplegic hyperopic and myopic autorefraction revealed mean sphere of +1.45 and -4.06 diopter with correlation coefficient of 0.95 and 0.99 respectively. Non-cycloplegic hyperopic autorefraction showed 74.2% sensitivity and 8.3% specificity at >-1 diopter with area under curve of 0.517 (p<0.0001). Cycloplegic hyperopic autorefraction showed 100% sensitivity and 97.1% specificity at >+1.85 diopter with accuracy of 0.616. Non-cycloplegic myopic autorefraction showed 100% sensitivity and 0.91% specificity at >-0.75 diopter with accuracy of 0.889. Cycloplegic myopic autorefraction showed 100% sensitivity and specificity at >-1.25 diopter with perfect accuracy. Conclusion: Non-cycloplegic hyperopic autorefraction failed to identify true negative cases. Cycloplegic autorefraction identified true positive cases and myopic autorefraction was relatively unaffected by cycloplegia.